Meningkatkan Kualitas Pendidikan dan Karakter Siswa melalui Program Bimbingan Belajar dan Konseling bagi Anak-Anak TK Kristen Setia Bulaya - Benny Zakaria; Hasahatan Hutahaean; Refamati Gulo (Lembaga Pengembangan Kinerja Dosen, 2025)
The lack of access to learning in schools leads to a decline in children's interest in studying. This has become a problem experienced by the children of Dusun Bulaya, Ilan Batu Uru Village, West Walendrang District, Luwu Regency, South Sulawesi Province. As a result, many children drop out of school. The lack of guidance and counseling at home and in school causes a decrease in children's motivation to continue learning. This issue underlies the activities that will be carried out by the community service program; these activities are conducted to educate and shape children's character so that they become more independent and optimal during their early educational years. Early childhood education plays an important role in forming the foundation of children's character and academic abilities. This study aims to explore the effectiveness of tutoring and counseling programs in improving the quality of education and the character of children at TK KRISTEN SETIA Bulaya. The method used is a descriptive qualitative approach, with the technique Observation, interviews, and documentation are used as data collection instruments. The research results indicate that tutoring programs can enhance students' basic academic understanding, while counseling services help develop positive attitudes, empathy, and discipline from an early age. Collaboration between teachers and parents is key to the success of this program. In conclusion, the integrated combination of tutoring and counseling significantly contributes to improving the quality of education and the character development of kindergarten children.